VD_FINDINFO HC / 2012 / 477 vom 9. Juli 2012 - VD Tribunal cantonal (2012)
ACTE DE NON-CONCILIATION, DÉLAI LÉGAL, FÉRIES JUDICIAIRES, SUSPENSION DU DÉLAI | 145 al. 2 let. a CPC (CH), 209 CPC (CH), 308 al. 2 CPC (CH), 318 al. 2 CPC (CH)